Evaluation of Technologies for the Co-Extraction of Phenolic Compounds and Proteinaceous Material from Olive-Derived Biomasses - María del Mar Contreras; Irene Gómez-Cruz; Inmaculada Romero; Eulogio Castro (Biology and Life Sciences Forum, 2021)
The current interest in using olive biophenols to promote functional ingredients and antioxidant additives is increasing. These compounds can be obtained from olive fruit and olive-derived biomasses using different technologies. However, other components can be co-extracted. Therefore, the main objective of this study was to evaluate the effect on protein solubilization of several extraction technologies, which were applied to obtain olive biophenols from olive-derived biomasses. For this purpose, conventional (Soxhlet and water bath) and non-conventional technologies (ultrasound and microwave) were evaluated. The total phenolic content was measured using the Folin and Ciocalteu method and the protein content was measured using the Dumas combustion method. The phenolic profile and the hydroxytyrosol content were also determined. Overall, the highest total phenolic content was obtained using the Soxhlet method, while the microwave-assisted extraction at 100 °C led to the highest protein solubilization (closer to 60%) using water.